Multi-controller balancing deployment strategy based on reliability evaluation in SDN - Tao HU; Jian-hui ZHANG; Teng MA; Wei ZHAO (Tongxin xuebao)
The control plane has low reliability and controller loads were unbalanced in distributed software defined networks,and a multi-controller balancing deployment strategy based on reliability evaluation was proposed.Firstly,node reliability was evaluated by weighting node efficiency and path quality,optimizing the controller location with balancing factor.Then based on improved k-center clustering,the redundant functions was introduced and the switch allocation was completed according to node attractiveness degree and controller load balancing rate,achieving a reasonable SDN sub-domain planning.The simulations show that compared with the existing strategy the number of required controllers is reduced by an average of 22.1%.The control plane elasticity is enhanced,and the controller load balancing performance has been improved significantly.